2018
DOI: 10.1007/s00068-018-0912-0
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cholecystostomy for severe (Tokyo 2013 stage III) acute cholecystitis

Abstract: This study confirms that PC is a valuable tool in the treatment of severe AC. Randomized trials are needed to clarify the criteria for patient selection and to optimize the timing for both cholecystostomy and cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
10
1
2
Order By: Relevance
“…We suppose that PC placement causes bile leakage or a foreign body reaction and aggravates pericystic scarring, making it difficult to complete laparoscopic surgery 19 . Second, during the waiting period before delayed surgery, more than a few patients have had recurrent symptoms or dislodgement of the drainage tube, both of which require reintervention 16,20 . An operation might be more difficult if a patient has developed recurrent symptoms due to an additional change in the pericystic inflammatory response 5 .…”
Section: Discussionmentioning
confidence: 99%
“…We suppose that PC placement causes bile leakage or a foreign body reaction and aggravates pericystic scarring, making it difficult to complete laparoscopic surgery 19 . Second, during the waiting period before delayed surgery, more than a few patients have had recurrent symptoms or dislodgement of the drainage tube, both of which require reintervention 16,20 . An operation might be more difficult if a patient has developed recurrent symptoms due to an additional change in the pericystic inflammatory response 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The Tokyo guidelines for management of AC recommend laparoscopic cholecystectomy as treatment for most patients with AC regardless of severity grade . Although this is the overriding recommendation, the guidelines also accept that PC plays an important role in the management of patients with AC deemed too high risk to withstand surgery, whether due to acute or chronic concurrent medical illness . Although several studies have confirmed the safety of PC in high‐risk patients, there is currently no consensus as how to best follow up these patients and ultimately at what time or whether at any stage they should be offered definitive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous cholecystostomy (PC) is a well‐established management option for the treatment of acute cholecystitis (AC). Most commonly, it is selectively utilized in patients deemed too high risk for operative management or as a sepsis control measure, followed by interval cholecystectomy . The long‐term outcome for these patients is poorly understood and this study was designed to determine the status of this patient cohort 12 months after the PC.…”
Section: Introductionmentioning
confidence: 99%
“…Þetta var gert hjá rúmlega 70% sjúklinga í þessari rannsókn sem er svipað hlutfall og gerist í erlendum rannsóknum. [16][17][18][19] Hjá 11 sjúklingum var ekki tekið fram hvernig keri var lagður og ekki var haegt að staðfesta legu hans síðar þegar myndrannsóknir voru yfirfarnar. Keri þessara 11 sjúklinga var lagður ómstýrt en erfitt getur verið að túlka ómskoðunarmyndir sem vistaðar eru við rannsókn og því mikilvaegt að þetta sé tekið fram í röntgensvari.…”
Section: Umraeðurunclassified
“…Samkvaemt þessu er 30 daga dánartíðni 6% sem er sambaerilegt við aðrar rannsóknir sem hafa sýnt fram á dánartíðni á bilinu 5-20% hjá sjúklingum sem fá kera sem meðferð við gallblöðrubólgu. 14,[17][18][19] Líkt og í okkar rannsókn hefur dánartíðnin í þessum rannsóknum verið rakin til alvarleika gallblöðrubólgunnar frekar en að tengjast ísetningu kera. 12 Tilgangur rannsóknarinnar var að skoða tíðni á notkun kera í gallblöðru við bráðri gallblöðrubólgu og fylgikvillum þeirrar meðferðar.…”
Section: Umraeðurunclassified